Respon Histopatologis Hepar Mencit (Mus musculus) yang Diinduksi Benzo(α)Piren terhadap Pemberian Taurin dan Ekstrak Daun Sirsak (Annona muricata) - Agata, Annisa; Widiastuti, Endang Linirin; Susanto, G. Nugroho; ', Sutyarso (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2016)
Cancer is a disease that is characterized by the existence of damage and cell abnormality in growth and differentiation. Liver cancer is a disorder of hepar tissue derivated from its tumors. Taurine is known as antioxidant but its role as anticancer needs to be explored more as well the role of Annona muricata leaf extract which is believed to have its role as anticancer substance. This research, therefore, aimed to explore the effect of taurine and Annona muricata leaf extract on the hepar histopathology of male mice (Mus musculus) induced by benzo(α)pyren in vivo. This research was carried out by using a complete randomized design, which consisted of 5 treatment groups which was repeated 5 times. Group I was given 0.2 mL corn oil for 15 days, group II was induced by benzo(α)pyren without taurin nor A. Muricata leaf extract for 10 days, group III was given 7.8 mg taurine/BW/day (twice a day) starting from the 15 th days before the induction of benzo(α)pyren, group IV, after induced with benzo(α)pyren, taurine was given with dosage of 7.8 mg/BW/day, group V, after induced with benzo(α)pyren, soursop leaf extract was given with amount of 277.8 mg/BW/day. Data analyzed by Kruskal-Wallis test and one way ANOVA with Fisher test (p>0.05). The results indicated that taurine had ability to recover the liver tissue induced by benzo(α)pyren as (carcinogenic) while, Annona muricata leaf extract had not shown any recover of tissue damage